Elastic and structural studies on (95-x)TeO₂-5La₂O₃-xTiO₂ lanthanum tellurite and xLi₂O-(100-X)[0.65GeO₂.O35PbO]lead germanate glasses / Izyan Nuraini Sapian - Sapian, Izyan Nuraini (2016)
Lanthanum tellurite and lead germanate glasses with compositions (95-x)TeO₂-5La₂O₃-xTiO₂ (x = 0 mol% to 20 mol%) and xLi₂O-(100-X)[0.65GeO₂.O35PbO] (x = 0 mol% to 40 mol%) were prepared by the melt quenching method, respectively. Elastic and structural properties of the glasses were studied by measuring sound velocity using the pulse-echo-overlap technique and Fourier Transform Infrared (FTIR) spectroscopy, respectively. For (95-x)TeO₂-5La₂O₃-xTiO₂ (x = 0 mol% to 20 mol%) samples, ultrasonic velocity measurements showed both independent moduli (Cʟ and μ ) and related elastic moduli such as bulk modulus (Kₑ), Young's modulus, hardness and Debye temperature were observed to increase gradually for x < 15 mol% followed by a large increase at x = 20 mol% addition of TiO₂. The results obtained showed that this glass system becomes more stable, rigid and stiffer with addition of TiC>2. Structural analysis showed increase in bridging-oxygen (BO) compared to non-bridging oxygen (NBO). Differential Scanning Calorimetry (DSC) measurements showed Tg increased with addition of TiO₂ and confirms the increasing rigidity of the network…